Enhanced Glial Reaction and Altered Neuronal Nitric Oxide Synthase are Implicated in Attention Deficit Hyperactivity Disorder - Zhang, Peng; Fang, Huyue; Lou, Chengjian; Ye, Shan; Shen, Guanghong; Chen, Shijia; Amin, Nashwa; Botchway, Benson O. A.; Fang, Marong (Frontiers in Cell and Developmental Biology, 2022)
Attention deficit hyperactivity disorder (ADHD) has a complex etiology, and its specific causal factors remain to be elucidated. Aberration of nitric oxide synthase (nNOS) and inflammation, together with astrocytic and microglial cells have been continually associated with several neurological disorders, including ADHD. Using spontaneously hypertensive rat (SHR), we investigated the changes in nNOS, inflammatory, microglial and astrocytic markers in the frontal cortex and hip-pocampus at three different ages: onset of hypertension stage (i.e., 6 weeks after birth of SHR), established hypertension stage (i.e., 12 weeks after birth of SHR) and senescent stage (i.e., 12 months after birth of SHR), and compared with its age-matched normotensive control, Wistar-Kyoto (WKY) rats. A significant upregulation of Iba-1 expression in the senescent stage of SHR was observed. Further, we observed an upregulated nNOS expression in both onset and established stages of SHR, and a downregulated nNOS in the senescent stage. Our study showed an age-related increment of astrogliosis in the cortex and hippocampi of aged SHR. On the basis of our results, alterations in the nNOS and Iba-1 expressions, as well as age-related astrogliosis, may contribute to ADHD pathogenesis